Acute metabolic, mechanical, and perceptual responses to curve versus linear repeated-sprint training in highly trained youth soccer players - Baena-Raya, A.; Ruiz-Zaragoza, J. M.; Díez-Fernández, D. M.; Rey, E.; Soriano, M. A.; Pérez-Castilla, A.; Rodríguez-Pérez, M. A.; Padrón-Cabo, A. (International Journal of Sports Physiology and Performance, 2026)
Purpose: This study aimed to (1) evaluate the acute metabolic, mechanical, and perceptual responses to curve versus linear repeated-sprint-training (RST) protocols in highly trained youth soccer players and (2) analyze whether the sprint trajectory influences the time course of recovery following RST protocols.